Measurement of the top quark mass with lepton+jets final states using p p collisions at s = 13 TeV - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; et al. (The European physical journal. C, Particles and fields, 2018)
The mass of the top quark is measured using a sample of t t ¯ events collected by the CMS detector using proton-proton collisions at s = 13 TeV at the CERN LHC. Events are selected with one isolated muon or electron and at least four jets from data corresponding to an integrated luminosity of 35.9 fb - 1 . For each event the mass is reconstructed from a kinematic fit of the decay products to a t t ¯ hypothesis. Using the ideogram method, the top quark mass is determined simultaneously with an overall jet energy scale factor (JSF), constrained by the mass of the W boson in q q ¯ ' decays. The measurement is calibrated on samples simulated at next-to-leading order matched to a leading-order parton shower. The top quark mass is found to be 172.25 ± 0.08 (stat+JSF) ± 0.62 (syst) GeV . The dependence of this result on the kinematic properties of the event is studied and compared to predictions of different models of t t ¯ production, and no indications of a bias in the measurements are observed.